Phenomenology Study of Early Childhood Grandparenting in Bali - Ni Luh Trada Pratiwi; Luh Ayu Tirtayani; Ni Nyoman Ganing (Journal of Psychology and Instruction, 2020)
Grandparenting is a part of parenting that is done by grandparents in the family to substitute the role of parents. This study aims at investigating the role of grand-parenting in early childhood education in the South Bali tourism area. This study implemented qualitative research method through phenomenological approach. Observation and interview were conducted to collect the data. Five subjects were selected through purposive-theoretical sampling, with the following criteria: (1) Hindu grandparents in the traditional village of Legian, (2) live and raised in the traditional village of Legian, (3) having grandchildren who study in early childhood education, (4) active and directly involved in parenting. The result of study revealed that grandparents have several roles in early childhood education, including: affection, education, social support, religious and cultural values. Self-monitoring is required to maximize the fulfillment of parenting. The implementation of grandparenting is influenced by the cultural value system (Tri Kaya Parisudha) as a nurturing foundation in shaping children's character. These concepts are inseparable from the implementation of grandparenting in Legian traditional village